IMPACT OF SOCIAL MEDIA MARKETING TOWARDS BUSINESS PERFORMANCE OF MSMES IN MANADO DURING COVID-19 PANDEMIC - Joseph, Omega P.; Tulung, Joy E.; Wangke, Shinta (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: The increasing use of the internet and social media today could be a good opportunity for MSMEs to market their products or services. Especially during the pandemic covid-19. MSMEs cannot directly interact with customers, whether to market products or to sell products because government required some community activities to be done from home. The purpose of the research is to find out deeper and further the social media marketing role on the business performance of SMEs in Manado during pandemic covid-19. This research used descriptive qualitative methodology and samples used in this research is 15 respondent who runs culinary MSMEs. The results shows that Social Media Marketing has positive impact towards Business Performance on Micro Small and Medium – Sized Enterprises (MSMEs) in Manado. Recommendations concluded for this research are to use and utilize social media in marketing products and a business. For the government can provide seminars or training about social media marketing so that MSMEs in Manado can continue to grow. Keywords: social media marketing, content creation, content sharing, interaction, accessibility, credibility, MSMEs, business